2009
DOI: 10.1203/pdr.0b013e3181be9e7e
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Released From Mother's Milk Has Antioxidant Properties

Abstract: Bioactive factors in human milk (HM) are crucial to the health of newborns, especially preterm infants. These compounds assist in reducing the oxidative stress that may occur as a result of combined exposure to supplemental oxygen and immature physiologic defenses. To identify the components in HM that contribute to its greater resistance to oxidative stress compared with infant formulae, enzymatic hydrolysates of HM were prepared, ultrafiltered, separated, and analyzed for antioxidant potential. The antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 35 publications
2
57
0
1
Order By: Relevance
“…XO inhibition in the 40 % ACN fraction was higher than that of GLF-240 min hydrolyzate, suggesting that a more potent fraction has been isolated with activated carbon. Previous studies have demonstrated the antioxidant potential of Trp and a Trp rich fraction from human mother's milk in vitro [84]. However, these results did not translate in a similar effect in a cell culture model of Caco 2 cells, showing a prooxidant activity of Trp and the Trp rich fraction which was dose-dependent [20].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…XO inhibition in the 40 % ACN fraction was higher than that of GLF-240 min hydrolyzate, suggesting that a more potent fraction has been isolated with activated carbon. Previous studies have demonstrated the antioxidant potential of Trp and a Trp rich fraction from human mother's milk in vitro [84]. However, these results did not translate in a similar effect in a cell culture model of Caco 2 cells, showing a prooxidant activity of Trp and the Trp rich fraction which was dose-dependent [20].…”
Section: Discussionmentioning
confidence: 82%
“…These results demonstrate that XO inhibition by the dipeptides was mainly due to the Trp residue. A Trp rich containing fraction from human mother's milk has previously been described for its antioxidant properties in vitro [84]. Certain amino acid structures have been correlated with high antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, oxidative tissue damage has been induced by excessive amounts of reactive oxygen species (ROS) (Kohen & Nyska, 2002). An in vitro study demonstrated that Trp inhibited the generation of ROS through the Fe(II)/CumOOH system (Tsopmo et al, 2009). These data suggest that Trp plays a role in inhibition of muscle oxidation and may therefore influence the flesh quality of fish; this potential role is worthy of investigation.…”
Section: Introductionmentioning
confidence: 99%